Early and middle woodland landscapes of the Southeast - Wright, Alice P.; Henry, Edward R. (Ripley P. Bullen series., 2013)
Integrates empirical data with social structural notions such as persistent, ritual, cultural, and social places, striving to explore the totality of landscape experiences across temporal and spatial spaces in the American Southeast.